From lymphopoiesis to plasma cells differentiation, the age-related modifications of B cell compartment are influenced by “inflamm-ageing” - Bulati, Matteo; Caruso, Calogero; Colonna-Romano, Giuseppina (Ageing research reviews, 2017)
•The leading cause of the age-related impairment of B cell compartment is inflamm-ageing.•In aged there is a dramatic decrease in circulating B lymphocytes, which is a part of the cluster of “IRP”.•Aged individuals are characterized by a less efficient ability to respond to new encounter antigens or vaccines.•Aged people and chronic inflamed subjects show the increase of a B cell population with a senescent/exhausted phenotype.•The study of B cells could be an important tool for monitoring both immunosenescence and chronic inflammatory diseases. Ageing is a complex process characterized by a general decline in physiological functions with increasing morbidity and mortality. The most important aspect of ageing is the chronic inflammatory status, named “inflamm-ageing”, strictly associated with the deterioration of the immune function, termed “immunosenescence”. Both are causes of increased susceptibility of elderly to infectious diseases, cancer, dementia, cardiovascular diseases and autoimmunity, and of a decreased response to vaccination. It has been widely demonstrated that ageing has a strong impact on the remodelling of the B cell branch of immune system. The first evident effect is the significant decrease in circulating B cells, primarily due to the reduction of new B cell coming from bone marrow (BM) progenitors, as inflammation directly impacts on B lymphopoiesis. Besides, in aged individuals, there is a shift from naïve to memory immunoglobulins production, accompanied by the impaired ability to produce high affinity protective antibodies against newly encountered antigens. This is accompanied by the increase of expanded clones of B cells, which correlates with poor health status. Age-related modifications also occur in naïve/memory B cells subsets. Indeed, in the elderly, there is a reduction of naïve B cells, accompanied by the expansion of memory B cells that show a senescence-associated phenotype. Finally, elderly show the impaired ability of memory B cells to differentiate into plasma cells. It can be concluded that inflammation is the leading cause of the age-related impairment of B cell compartment, which play certainly a key role in the development of age-related diseases. This makes study of B cells in the aged an important tool for monitoring immunosenescence, chronic inflammatory disorders and the effectiveness of vaccines or pharmacological therapies.